Sentinel lymph node identification using superparamagnetic iron oxide particles versus radioisotope: The French Sentimag feasibility trial. Issue 5 (12th January 2016) - Houpeau, Jean‐Louis; Chauvet, Marie‐Pierre; Guillemin, François; Bendavid‐Athias, Cécile; Charitansky, Hélène; Kramar, Andrew; Giard, Sylvia
Abstract : Background and Objectives: The French Sentimag feasibility trial evaluated a new method for the localization of breast cancer sentinel lymph node (SLN) using Sienna+®, superparamagnetic iron oxide particles, and Sentimag® detection in comparison to the standard technique (isotopes ± blue dye). Methods: We conducted a prospective multicentric paired comparison trial on 115 patients. SLN localization was performed using both the magnetic technique and the standard method. Detection rate and concordance between magnetic and standard tracers were calculated. Post‐operative complications were assessed after 30 days. Results: Results are based on 108 patients. SLN identification rate was 98.1% [93.5–99.8] for both methods, 97.2% [92.1–99.4] for Sienna+® and 95.4% [89.5–98.5] for standard technique. A mean of 2.1 SLNs per patient was removed. The concordance rate was 99.0% [94.7–100.0%] per patient and 97.4% [94.1–99.2] per node. Forty‐six patients (43.4%) had nodal involvement. Among involved SLNs, concordance rate was 97.7% [88.0–99.9] per patient and 98.1% [90.1–100.0] per node. Conclusions: This new magnetic tracer is a feasible method and a promising alternative to the isotope. It could offer benefits for ambulatory surgery or sites without nuclear medicine departments. J. Surg. Oncol. 2016;113:501–507 . © 2016 Wiley Periodicals, Inc.